First platinum(II)-based metal-organic linker technology (Lx®) for a plug-and-play development of antibody-drug conjugates (ADCs). (3rd August 2019) - Merkul, Eugen; Sijbrandi, Niels J.; Muns, Joey A.; Aydin, Ibrahim; Adamzek, Kevin; Houthoff, Hendrik-Jan; Nijmeijer, Bart; Van Dongen, Guus A.M.S.
ABSTRACT: Introduction : Compared to the antibody and drug components of an ADC, the linker part has been somewhat neglected. However, its importance for the reduction of failures in ADC approvals is increasingly recognized. Next of being a stable glue between drug and antibody, an ideal linker should improve the manufacturability and widen the therapeutic window of ADCs. Areas covered : The biopharmaceutical company LinXis started an ADC development program in which platinum(II) is the key element of the first metal-organic linker. The cationic complex [ethylenediamineplatinum(II)] 2+, herein called ' Lx ®', is used successfully for conjugation of drugs to antibodies. Expert opinion : Based on lessons learned from ADC development, Lx linker technology fulfills most of the desirable linker characteristics. Lx allows large-scale cost-effective manufacturing of ADCs via a straightforward two-step 'plug-and-play' process. First clinical candidate trastuzumab- Lx -auristatin F shows favorable preclinical safety as well as outstanding in vivo tumor targeting performance and therapeutic efficacy.